2021
DOI: 10.1007/s10803-021-05256-6
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Sensory Subgroups in Typical Development and Autism Spectrum Development Using Factor Mixture Modelling

Abstract: This study uses factor mixture modelling of the Short Sensory Profile (SSP) at two time points to describe subgroups of young autistic and typically-developing children. This approach allows separate SSP subscales to influence overall SSP performance differentially across subgroups. Three subgroups were described, one including almost all typically-developing participants plus many autistic participants. SSP performance of a second, largely-autistic subgroup was predominantly shaped by a subscale indexing beha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 67 publications
(106 reference statements)
0
3
0
Order By: Relevance
“…This study utilizes data overlapping with a sample of children included in prior research on sensory classes in autism and typical development (TD) based on longitudinal data between two time points (2–5 years (160 ASD, 85 TD); 4–10 years (87 ASD, 55 TD); Dwyer et al, 2020). Past research also examined differences in anxiety and sleep problems between sensory classes derived using factor mixture modeling (Dwyer et al, 2021). The present cross-sectional study is distinct from these prior longitudinal studies in several ways.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study utilizes data overlapping with a sample of children included in prior research on sensory classes in autism and typical development (TD) based on longitudinal data between two time points (2–5 years (160 ASD, 85 TD); 4–10 years (87 ASD, 55 TD); Dwyer et al, 2020). Past research also examined differences in anxiety and sleep problems between sensory classes derived using factor mixture modeling (Dwyer et al, 2021). The present cross-sectional study is distinct from these prior longitudinal studies in several ways.…”
Section: Introductionmentioning
confidence: 99%
“…Third, although various SSP factor structures have been suggested (e.g. Dwyer et al, 2021; Z. Williams et al, 2018), we elected to use the original seven SSP subscales (McIntosh et al, 1999), which are more frequently used in clinical settings and may therefore provide more clinically relevant information.…”
Section: Introductionmentioning
confidence: 99%
“…However, only a few studies have discovered a relationship between SPD and sleep disturbances which opposes our study. 24,41,42,43 For SPD among children with ASD, Dwyer, et al (2021) summarize that children with ASD scored lower in SSP and displayed increased sleep disturbances. This may be because their study explores sleep disturbances in the longitudinal period through the EEG compared to our study which only evaluates using a questionnaire at a point in time.…”
Section: Discussionmentioning
confidence: 97%
“…Less positively, studies have also reported that autistic people with sensory reactivity are more likely to experience sleep problems (Dwyer et al, 2022;Han et al, 2022;Linke et al, 2021), and hyper-reactivity to sensory input may predict sleep difficulties later in life (Manelis-Baram et al, 2022;Mazurek et al, 2019). Although prior studies have yielded inconsistent outcomes with respect to those sensory modalities most critical for exacerbating sleep problems (Linke et al, 2021;Manelis-Baram et al, 2022;Tzischinsky et al, 2018), it appears that auditory filtering is a contributing factor (Hollway et al, 2013;Wang et al, 2019).…”
Section: Auditory Processing and Non-social Traitsmentioning
confidence: 99%